Development of Inquiry-Based Mechanics Teaching Materials to Train Critical Thinking Skills for FKIP Physics Students, Universitas Pattimura Ambon - Heppy Sapulete; Fryan Sopacua (Britain International for Academic Research (BIAR) Publisher, 2021)
This research is to produce inquiry-based mechanics teaching materials to train critical thinking skills of Physics FKIP students, Pattimura University, Ambon. The research design used the Kemp model (1994) and the learning process was packaged in an inquiry setting with a total sample size of 26 students in the 2020/2021 school year. The data collected were in the form of teaching material validation data, critical thinking skills test instrument validation data, critical thinking skills data, and student response data. The data analysis techniques used include: qualitative descriptive analysis including: the results of validation of teaching materials, the results of instrument validation tests of critical thinking skills, the results of critical thinking skills, and the results of student responses. The results showed that: 1) the validity of the student teaching materials developed was categorized as valid; 2) the validity of the developed critical thinking skills test instrument was categorized as valid; 3) in the percentage of critical thinking skills there is an increase in value from pretest to posttest by more than 40%; 4) Student responses to teaching materials and the implementation of learning are very positive and the lowest percentage is obtained, namely 85% satisfaction with a very good assessment. Based on the results, it can be concluded that the development of inquiry-based mechanics teaching materials can train critical thinking skills of Physics FKIP students, Pattimura University, Ambon.